Pengaruh Work-Family Conflict terhadap Performa Kerja Petugas Pemadam Kebakaran pada Dinas PMK Surabaya - Hadi, Hafid Kholidi (BISMA (Bisnis dan Manajemen), 2018)
This research is aim to investigate the influence of Work-family conflict toward work performance of firefighters office in Surabaya. Firefighters have uncertainty work hours and face high risk in every wildfire. They also have to safe other people life. Because of that Work-family conflict is easily happen to them. With Quantitative approach, this research using survey and distribute questionnaire to 190 firefighters in 5 firefighters office around Surabaya. The result is Work-family conflict and family work conflict have significant negative effect to employee work performance. Other findings there are variables that decrease the effect of Work-family conflict, supervisor support and spousal support. Supervisor support decrease the effect of Work-family conflict to work performance, and spousal support decrease the effect of family-work conflict to work performance